A three-dimensional study of the glottal jet - Krebs, F. (2012)
This work builds upon the efforts to characterize the three-dimensional features of the glottal jet during vocal fold vibration. The study uses a Stereoscopic Particle Image Velocimetry setup on a self-oscillating physical model of the vocal folds with a uniform vocal tract. Time averages are documented and analyzed within the framework given by observations reported for jets exiting elongated nozzles. Phase averages are locked to the audio signal and used to obtain a volumetric reconstruction of the jet. From this reconstruction, the intra-cycle dynamics of the jet axis switching is disclosed.